Ram-jet combustion based on shock/flame interaction - Edwards, J. A. (Cranfield University, 1983)
An experimental investigation into the effects of shock/wake and shock/flame interaction on the base pressure of axisymmetric bodies at Mach 2 has been carried out. This investigation has determined the effects of various forms of shock generator (axisymmetric cowls, twodimensional wedges and 'delta' wings) on the base pressure. Shock waves generated by over-expanding the airflow in an open-jet wind tunnel have been used to determine the effect of shock strength on the base pressure of an axisymmetric fuel injector. Both peripheral bleed and axial bleed of hydrogen fuel have been examined and the effect of shock compression on the resulting flame has been determined. In the axial bleed case nitrogen and hydrogen bleed without combustion has also been examined. The effect of varying the airflow stagnation temperature has also beeninvestigated. It is demonstrated herein that there is a distinct shock/wake interaction position that maximises the base pressure, that with interaction at this optimal position the static pressure rise across the shock wave can be communicated in full to the base of the centrebody, and that favourable aerodynamic interference between the wake and a cowl of 50 convergent-divergent internal section can give rise to a net drag reduction. The shock/wake and shock/flame experiments demonstrate that a significant base thrust can be generated, however, the fuel efficiency decreases with increasing shock strength. It is shown that the fuel specific impulse is a function of shock strength, interaction position and bleed mode (peripheral or axial). The onset of boundary layer separation due to the adverse pressure gradient encountered when the base pressure is high appears to limit the useful addition of wake combustion. Finally, it is demonstrated that the base pressure, with and without combustion, is only a weak function of airflow stagnation temperature.